Circular Slotted Antenna with CPW feed for GSM and UWB Applications - Kumar, Sanjeev; Kumar, Ravi; Nandan, Durgesh (International Journal of Sensors Wireless Communications and Control, 2021)
Background & Objective: The circular slotted monopole microstrip antenna with Coplanar Waveguide (CPW) feed for unified GSM and Ultra-Wideband (UWB) applications have been presented in this article. Circular shaped slots have been embedded in the radiating patch. Less surface area has been found due to slots etching and the overall antenna size is reduced by 45%. Results: The proposed antenna demonstrates a double band operation wrapping 883.6-1206 MHz (GSM band) and 2.75-18.30 GHz (UWB, X, and Ku) frequency band with VSWR of less than 2 and fractional B. W. of 30.8 % and 147% respectively. The pattern of radiation presented by the antenna is nearly omnidirectional in H-plane and directional in E-plane within the GSM and UWB band. Conclusion: There is a variety of applications nowadays using these UWB antennas such as modern civil and military applications, wireless and radar communications, etc. Measured results are presented to validate the proposed antenna structure, which shows that the proposed designed antenna structure has a stable radiation pattern both at the GSM and UWB band ranges.
Keywords: UWB